2011
DOI: 10.1111/j.1420-9101.2011.02411.x
|View full text |Cite
|
Sign up to set email alerts
|

Fitness consequences of social network position in a wild population of forked fungus beetles (Bolitotherus cornutus)

Abstract: Social networks describe the pattern of intraspecific interactions within a population. An individual’s position in a social network often is expected to influence its fitness, but only a few studies have examined this relationship in natural populations. We investigated the fitness consequences of network position in a wild beetle population. Copulation success of male beetles positively covaried with strength (a measure of network centrality) and negatively covaried with clustering coefficient (CC) (a measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
97
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(97 citation statements)
references
References 59 publications
(107 reference statements)
0
97
0
Order By: Relevance
“…By influencing behavioural traits, foraging success and disease status, social network position will often be fundamental in determining body condition, stress levels (Brent, Semple, Dubuc, Heistermann, & MacLarnon, 2011) and ultimately reproductive success (Formica et al, 2012;McDonald, 2007;Wey et al, 2013). In this regard, demonstrating the potential of using social network approaches in systems in which many individuals are not identifiable is highly important.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…By influencing behavioural traits, foraging success and disease status, social network position will often be fundamental in determining body condition, stress levels (Brent, Semple, Dubuc, Heistermann, & MacLarnon, 2011) and ultimately reproductive success (Formica et al, 2012;McDonald, 2007;Wey et al, 2013). In this regard, demonstrating the potential of using social network approaches in systems in which many individuals are not identifiable is highly important.…”
Section: Discussionmentioning
confidence: 98%
“…Social network analysis is now widely used to study animal social behaviour (Farine, Garroway, & Sheldon, 2012;PinterWollman et al, 2013;Sih, Hanser, & McHugh, 2009;Wey, Blumstein, Shen, & Jord an, 2008), and is fast developing beyond being a descriptive tool to become fundamental in quantifying behavioural interactions and their subsequent consequences in a wider social context (Dey, Reddon, O'Connor, & Balshine, 2013;Formica et al, 2012;Kohn, King, Dohme, Meredith, & West, 2013;Sueur, Jacobs, Amblard, Petit, & King, 2011;Wey, Burger, Ebensperger, & Hayes, 2013). There is a growing focus on understanding how an individual's personality, phenotype and condition interact to influence its social decision making and social strategy (Aplin et al, 2013;Croft et al, 2005Croft et al, , 2009Silk, Croft, Tregenza, & Bearhop, 2014;Wilson, Krause S., Dingemanse & Krause 2013).…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…Factor analysis revealed that only measures of male and alpha female network position were associated with new eggs (table 1 and figure 2a). Simple, dyadic interactions between the dominant male and female were not associated with new eggs, demonstrating that unlike factor 3 with HS, for which dyadic agonism was illuminating, social network analysis provided unique insight [24]. Although we could not quantify individual female RS, these data suggest alpha females contributed the most reproductively, as expected for her status and size [16,60].…”
Section: Discussionmentioning
confidence: 91%